Peningkatan Kemampuan Membaca Permulaan Melalui Media Busy Book di TK B Hikari Serpong, Tangerang Selatan - Hayati, Miratul; Faeruz, Ratna; Rahma, Aenida Yasinta (Indonesian Journal of Islamic Early Childhood Education, 2019)
The ability to create or produce interesting media is needed, as an effort to increase children's desire to read, see, and read written symbols. This study aims to improve the ability of early reading through the use of the busy book media in children aged 5-6 years in TK Hikari, Serpong, Tangerang. This class action research uses the Kemmis and Mc Taggart cycle models and is done collaboratively. The research subjects consisted of 9 children aged 5-6 years from group B TK. Hikari. The object of the research is early reading ability. Data collection instruments used observation, rating scale, and documentation. Data analysis used quantitative descriptive and qualitative descriptive. The results of this study indicate that the use of busy book media can improve the ability of early reading in children aged 5-6 years. Increasing the early reading ability showed by the changes in some conditions, in language aspects, conventions of print, knowledge of letters, linguistic awareness, correspondence of graphical patterns, emergent reading, emergent writing, motivation to print, other cognitive skills. at 31.2% in the pre-cycle stage, to 50.9% at the first cycle stage, and to 77.3% at the second cycle stage. This research was stopped because it met the success criteria of more than 75%.